Upper limb movement control strategy of top-tier elite male badmintonplayers when smashing for different distances - Dong, Tengfei; Kim, Youngsuk; Seo, Jungsuk; Moon Kim, Dong; Kim, Sukwon (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Purpose. Mastering the skill of smashing in a game can be quite challenging. Unfortunately, it’s not always easy to controlthe distance of the smash. The present study investigated the impact of different smashing distances on muscle activationpatterns and kinematics of the upper limbs.Methods. Ten collegiate athletes from a top-ranked team in Korea participated in the present study with a mean age, weight,and height of 21 ± 1 years, 71.9 ± 9.1 kg, and 1.78 ± 2.24 m, respectively. Three valid data points for each subject at threedifferent distances were analyzed using a one-way analysis of variance (ANOVA).Results. The results demonstrated that with increasing smashing distance, the internal rotation angle of the elbow andwrist joints decreased, while the angular velocity of flexion and internal rotation of the shoulder, elbow, and wrist jointsincreased. Muscle activation increased for all muscles except the biceps brachii (BICLO) with increasing distance. The greatestchanges in activation levels were observed in the anterior deltoid (DELTA), extensor carpi radialis (ECR), and flexor carpiulnaris (FCU).Conclusions. During tasks with different smashing distances, muscle activation in the upper limbs (except the biceps)increased with increasing distances. Additionally, the internal rotation angle of the upper limbs decreased with increaseddistances, while the angular velocity of flexion and internal rotation of the shoulder, elbow, and wrist joints increased.
Keywords: mechanics; athletes; coordination; joints; badminton; sports skill